PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN KEPRIBADIAN GURU TERHADAP MOTIVASI BELAJAR SERTA IMPLIKASINYA PADA PRESTASI BELAJAR SISWA SMA NEGERI 1 PEUSANGAN KABUPATEN BIREUEN - Megawati Megawati; Kamaruddin Kamaruddin (LPPM-UNIKI, 2023)
The purpose of this study was to analyze the effect of the transformational leadership of the school principal and the teacher's personality on student motivation and its implications for student achievement. Research on students of SMA Negeri 1 Peusangan, Bireuen Regency. Using associative quantitative methods with path analysis tools. The results of the study prove: 1) There is a causal relationship between the principal's transformational leadership variables and the teacher's personality. 2) There is a direct and indirect effect of the principal's transformational leadership on student learning motivation of 38.52%. 3) There is a direct and indirect effect of the teacher's personality on student learning motivation of 22.96%. 4) The contribution of the principal's transformational leadership factor and teacher's personality to student learning motivation is 62,1%. 5) There is an influence of learning motivation on student achievement of 41.7%. 6) There is a direct and indirect effect of the principal's transformational leadership on student achievement of 20.66%. 7) There is a direct and indirect influence of the teacher's personality on student achievement of 42.17%. 8) Simultaneously the contribution of the transformational leadership of the principal and teacher's personality to the learning achievement of SMA Negeri 1 Peusangan, Bireuen Regency is 60,2%.